My Choreographer: An Augmented Reality Dance Training System - Singh Sidhu, Manjit; Iqbal, Javid (Multidisciplinary Applied Research and Innovation, 2021)
This innovative and one-of-a-kind user interface (UX) concept for a virtual fitness dance framework seeks to assist users in living a safe lifestyle. A variety of academics and businesses have created workout programmes that use a simulated coach to teach the individual what steps they can take. However, such applications can be challenging to correctly follow the interactive guide’s movements, and the guidance given to remind users of their proper body posture has limitations. This is due to the fact that most applications are designed for users to merely observe and follow a character’s movements (poses) from a third person viewpoint. Users in this dance training method will observe the exercise-postures of a virtual skilled trainer seen in first person and receive coaching in a step-by-step gesture. The preliminary study for dance and performance is based on the architecture of my choreographer (MC). More dance styles are being added to the library of the improved MDS prototype. The MC device architecture has been demonstrated through a series of trials to train dance trainees. The MC prototype has a lot of promise for promoting dancing, exercise, music, and social engagement. The MC method is intended for commercialization to dance training/culture centres and dance enthusiastic.